Emotional Neuroscience and Learning. An Overview - Gkintoni, Evgenia; Antonopoulou, Hera; Halkiopoulos, Constantinos (Technium Social Sciences Journal, 2023)
In recent years, there has been a growing interest in examining the effect of emotion on learning. The relationship between neuroscience and education is direct, and emotional neuroscience has a significant impact on the learning process. This study’s primary objective is to examine the connection between emotional neuroscience and the learning process. Therefore, the effects of emotion on cognitive function, memory, and learning processes were reviewed. A search was conducted using electronic databases (PubMed and Scopus). To emphasize the most recent literature, articles published within the last fifteen years were sought out. Based on the review of studies, it was determined that emotional neuroscience and learning have a strong correlation. Notably, both positive and negative emotions can have an impact on a person’s cognitive functions, with the greatest impact on attention, memory, and learning.